Liver Angiosarcoma: Rare tumour associated with a poor prognosis, literature review and case report. (2016) - Millan, Mauricio; Delgado, Alejandro; Caicedo, Luis A.; Arrunategui, Ana M.; Meneses, Carlos A.; Villegas, Jorge I.; Serrano, Oscar; Caicedo, Liliana; Duque, Mauricio; Echeverri, Gabriel J.
Highlights: Liver Angiosarcoma is rare and aggressive tumour that requires surgical management. Partial Hepatectomy is the ideal surgical management for Liver Angiosarcoma. Liver transplant does not improve the survival of Liver Angiosarcoma patients. Abstract: Introduction: Liver angiosarcoma is a very uncommon tumour of mesenchymal origin, representing between 0.1–2% of all primary tumours of the liver, affecting mainly men in their sixth or seventh decade of life, with a high mortality in the first years (Chaudhary et al., 2015). Literature reports of its surgical treatment vary from a total or partial hepatectomy with or without liver transplant. Presentation of case: A 37 year old male, with a 7 year history of a fatty liver, was found to have a 12 cm diameter tumour in a cirrhotic liver, during an abdominal Computed Tomography (CT) scan. Patient was asymptomatic with negative tumour markers, yet tumour liver biopsy revealed a Liver Angiosarcoma with positive immunohistochemistry for neoplastic cells CD31 and CD34. Patient was deemed candidate for a partial hepatectomy of the affected liver segments which was done without complications and no evidence of other tumour lesions was found during surgery. Patient continued oncologic management with ongoing chemotherapy. Discusion: Liver Angiosarcoma, although rare, persists with a high mortality due to its aggressive nature. Never the less liver transplantation, although proven to be an effective treatment for many pathologies that culminate in liver failure, fails to improve patients' survival and prognosis, when compared to partial hepatectomy as surgical management to for liver Angiosarcoma, Conclusion: Partial hepatectomy as surgical management, followed by adjuvant therapy, for Liver Angiosarcoma continues to prove favourable results and prognosis compared to Liver Transplantation.